2018
DOI: 10.1016/j.ydbio.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Convergence on reduced stress behavior in the Mexican blind cavefish

Abstract: Responding appropriately to stress is essential for survival, yet in pathological states, these responses can develop into debilitating conditions such as post-traumatic stress disorder and generalized anxiety. While genetic models have provided insight into the neurochemical and neuroanatomical pathways that underlie stress, little is known about how evolutionary processes and naturally occurring variation contribute to the diverse responses to stressful stimuli observed in the animal kingdom. The Mexican cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 85 publications
(112 reference statements)
11
60
0
Order By: Relevance
“…In addition, understanding stress and its effects in the long term on growth, cardiovasculature, metabolism, and musculature is important in aquaculture (Sadoul and Vijayan, 2016). We have previously demonstrated that adult A. mexicanus have diminished stress responses (Chin et al, 2018), and these data extend this to larval forms. We expect that future work using powerful approaches unique to larvae, such as whole brain functional imaging and tracing of neural circuits that modulate stress, together with genotype-phenotype associations between genes and stress responses will shed significant light into genetic pre-disposition to stress disorders.…”
Section: Future Directionssupporting
confidence: 70%
“…In addition, understanding stress and its effects in the long term on growth, cardiovasculature, metabolism, and musculature is important in aquaculture (Sadoul and Vijayan, 2016). We have previously demonstrated that adult A. mexicanus have diminished stress responses (Chin et al, 2018), and these data extend this to larval forms. We expect that future work using powerful approaches unique to larvae, such as whole brain functional imaging and tracing of neural circuits that modulate stress, together with genotype-phenotype associations between genes and stress responses will shed significant light into genetic pre-disposition to stress disorders.…”
Section: Future Directionssupporting
confidence: 70%
“…The volume of the pineal gland, a region associated with secretion of sleep-promoting melatonin, was significantly reduced in all three populations of cavefish (Fig 1K, Fig S4), raising the possibility that these changes are associated with loss of sleep and circadian regulation of activity in cavefish [39, 43]. In addition, volume of the habenular nuclei that regulate stress were reduced in all three cavefish populations, demonstrating a potential neuroanatomical mechanism underlying blunted response to stress in cavefish (Fig 1K, Fig S4) [44]. While many of the evolved changes in brain anatomy we identified were shared between cave populations, we also observed differences between individuals from different cave populations.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to directly compare brain activity in sleeping surface fish and cavefish, we pharmacologically induced sleep in all populations of cavefish. Previously, we showed that moderate concentrations of β-adrenergic antagonist propranolol and HCRT receptor inhibitor EMPA restore sleep to Pachón cavefish without affecting sleep in surface fish, suggesting enhanced sensitivity to inhibitors of β-adrenergic and HCRT signaling [44, 51]. The effects of these agents on neural activity and in additional cave populations is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence or absence of other fish can also affect a fish's overall swimming behavior, whether or not it is near another fish. For example, surface fish exhibit a stress response to isolation which makes them seek the bottom of their tank [6]. Although depth is not significant in our shallow tank, changes in the mean speed or turning statistics are.…”
Section: Group Size Affects Speed Regulation and The Nature Of Turnsmentioning
confidence: 90%